Shear Stress Ameliorates Superoxide Impairment to Erythrocyte Deformability With Concurrent Nitric Oxide Synthase Activation - Kuck, Lennart; Grau, Marijke; Bloch, Wilhelm; Simmonds, Michael J. (Frontiers in Physiology, 2019)
The cellular deformability of red blood cells (RBC) is exceptional among mammalian cells and facilitates nutrient delivery throughout the microcirculation; however, this physical property is negatively impacted by oxidative stress. It remains unresolved whether the molecular determinants of cellular deformability – which in the contemporary model of RBC are increasingly recognized – are sensitive to free radicals. Moreover, given cellular deformability has recently been demonstrated to increase following exposure to specific doses of mechanical stimulation, the potential for using shear “conditioning” as a novel method to reverse free-radical induced impairment of cell mechanics is of interest. We thus designed a series of experiments that explored the effects of intracellular superoxide (O2-) generation on the deformability of RBC and also activation of pivotal molecular pathways known to regulate cell mechanics – i.e., PI3K/Akt kinase and RBC nitric oxide synthase (NOS). In addition, RBC exposed to O2- were conditioned with specific shear stresses, prior to evaluation of cellular deformability and activation of PI3K/Akt kinase and RBC-NOS. Intracellular generation of O2- decreased phosphorylation of RBC-NOS at its primary activation site (Ser1177) (p < 0.001), while phosphorylation of Akt kinase at its active residue (Ser473) was also diminished (p < 0.001). Inactivation of these enzymes following O2- exposure occurred in tandem with decreased RBC deformability. Shear conditioning significantly improved cellular deformability, even in RBC previously exposed to O2-. The improvement in cellular deformability may have been the result of enhanced molecular signaling, given RBC-NOS phosphorylation in RBC exposed to O2- was restored following shear conditioning. Impaired RBC deformability induced by intracellular O2- may be due, in part, to impaired activation of PI3K/Akt, and downstream signaling with RBC-NOS. These findings may shed light on improved circulatory health with targeted promotion of blood flow (e.g., exercise training), and may prove fruitful in future development of blood-contacting devices.